Providing Psychological and Emotional Support After Perinatal Loss: Protocol for a Virtual Reality-Based Intervention - Corno, Giulia; Bouchard, Stéphane; Baños, Rosa M.; Rivard, Marie-Christine; Verdon, Chantal; de Montigny, Francine (Frontiers in Psychology, 2020)
The loss of an infant during the perinatal period has been recognized as a complex and potentially traumatic life event and can have a significant impact on women’s mental health. However, often times, psychological aftercare is typically not offered, and manualized interventions are rarely used in clinical care practice and have seldom been evaluated. In recent years, a growing number of studies have demonstrated the efficacy of virtual reality (VR) interventions to facilitate the expression and coping with emotions linked to a traumatic event. The objective of the proposed paper is to present the protocol of a randomized control trial aimed to assess a novel VR-based intervention for mothers who experienced a perinatal loss. We hypothesize that the VR-based intervention group will show significantly reduced symptoms related to grief, postnatal depression and general psychopathology after treatment relative to a treatment-as-usual (TAU) group. Participants would be randomly assigned to the TAU + VR or to the VR + TAU condition. The TAU condition as well as the VR-based intervention will last 3 weeks, after which women will complete a post-assessment. The proposed VR-based intervention will consist in three weekly sessions focused respectively on: 1) collect information about the loss and psychoeducation about perinatal grief, and introduction to the virtual environment; 2) through the use of the virtual environment, women will be assisted in the elaboration and acceptation of loss; 3) recreate, using the specific features of the virtual environment a positive metaphor representing woman’s future life. VR has proved to be a valid intervention tool in clinical psychology, and in the last years VR technologies have become more affordable to be used in clinical practice. With the present study we propose to answer to the unquestionable need for interventions addressed to ameliorate the emotional effects in women who experienced perinatal loss, by exploiting also the therapeutic opportunities offered by a new technology as VR.